Choose MyPlate: Reduce Your Sodium - Shari Bresin; D'Alicia Straughter; Karla Shelnutt; Gail Kauwell (EDIS)
This publication provides facts about sodium and the importance of reducing sodium intake. It also provides easy tips to reduce your sodium intake. Written by Ashley Hamm, Shari Bresin, D’Alicia Straughter, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised November 2021.